HUBUNGAN KEPATUHAN PERAWAT TERHADAP SOP TRANFUSI DENGAN KEPUASAN KELUARGA PASIEN - KUSDARWATI (LPPMK STIKES Widyagama Husada, 2022)
Compliance with SOP transfusion can increase patient satisfaction. The research design used in this study was a correlative study with a cross sectional approach. The population is all nurses, the sample is 36 respondents. The data were collected using observation sheets and questionnaires from the patient's family. Data analysis using Spearman Rho test with = 0.05. The results showed 27 [75%] nurses in the pediatric room/IRNA IV RSUD Dr. Saiful Anwar Malang complied with the transfusion SOP, while the patient's family as many as 18 respondents [50%] were satisfied and 10 respondents [28%] were very satisfied with the services provided by nurses. The results of the Spearman Rho stastic test showed a significant relationship between nurse compliance on the transfusion SOP with the patient's family satisfaction in the Children's Room/IRNA IV RSUD Dr. Saiful Anwar Malang with p value = 0.000 or p <0.05. Conclusion: Nurses' compliance in carrying out transfusion SOPs is related to patient's family satisfaction. Keywords: Satisfaction, Blood Transfusion SOP, Compliance K